Proposta de trabalho didático sobre o conteúdo enunciação reportada sob uma abordagem enunciativa - Valentim, Duane (2018)
In this research we aim to present a didactic exercise that explores the different kinds of reported enunciation considering the operation of epilinguistic activity during the process of teaching and learning, contributing to the linguistic development of the students when working with the possibilities of operating with the language. The didactic exercise considers the knowledge of the students about their own language by observing, redesigning and comparing the statements, we believe we can contribute to the linguistic and cognitive development of students, leading them to enrich the discursive relations in their texts. The proposed herein objectives have as theoretical framework the Theory of Predicative and Enunciative Operations (TOPE), initiated by Culioli. Such theoretical assumptions can contribute to the configuration of a productive approach during the process of teaching and learning because of its operative model of linguistic and non- classificatory analysis. Regarding the methodological concern for the development of this work, we set our guide based on a theory of linguistic observable, performed by an analytical framework composed of primitive, predicative and enunciative relations, in which are installed, respectively, notions of semantic, syntactical and enunciation. With regard to the analysis of our corpus, we were able to identify that, although there is no explanation through metalanguage, students use different justifications regarding to the use of reported speech and reveal to understand what is involved in the linguistic exercise. Therefore, we infer that although language activity supposes a constant epilinguistic work, certain didactic exercises emerge the epilinguistic activity of the individual that when observed at the linguistic level by the students and by the teacher, it is possible to allow the students to rationalize their way of thinking and also helps the teacher leading the students to operate on their own representations.